Data Migration from Libsys to Koha ILS: An Experimental Study - Sahoo, Sambhunath; Saikia, Mukesh (Journal of Information and Knowledge, 2019)
Library automation is one of the primary activities of all kinds of libraries. In this paper, we are focusing on academic library system. For library automation, academic libraries are using some Integrated Library Management System (ILMS) software that may be proprietary or open source. The question of data migration emerges when library administrators think of moving from an existing ILMS to a new ILMS. This paper aims to present a systematic approach for data migration from existing ILMS (Libsys) to a new ILMS (Koha) and it has been successfully experimented at Tezpur University library system. The study found that both bibliographical data and patron data in the new system (Koha) are identical with existing system (Libsys).